Design of the Gianyar – Amlapura 150 KV Tower Delivery Landslide Detection System - I Wayan Dikse Pancane (PT FORMOSA CENDEKIA GLOBAL, 2023)
In supporting tourism on the Island of the Gods, PLN personnel are expected to provide the best possible service to consumers. Therefore, the Bali Transmission System needs to provide a reliable transmission system that provides world-class services to electricity consumers in Bali. Current monitoring methods are not effective enough to monitor the critical condition of towers and are prone to landslides which can occur at any time, especially during the rainy season and extreme weather. The need for a reliable transmission system led researchers to the idea of ​​having monitoring equipment that can work in real time to detect the condition of the tower or the movement of the ground around the tower as quickly as possible. The measurement accuracy of the MPU6050 sensor reaches 98.8% which can be said to be very suitable as a sensor for detecting the angle of the slope of the ground, the slightest slope can be detected